Acute respiratory infections surveillance system evaluation, Mozambique, June-December, 2021 - Florência Vicente Chiconela Cossa; Gerson Afai; Nilsa Nascimento; Cristolde Atanásio Salomão; Auria Ribeiro Banze; Cynthia Semá Baltazar (Journal of Interventional Epidemiology and Public Health)
Background: COVID-19 is a public health emergency with a huge morbidity and mortality impact on the population, and rapid diagnostic testing is essential for controlling the disease. The study evaluated the surveillance system for acute respiratory infections in sentinel posts, Mozambique, from 01 June to 31 December 2021.